A 5-year old male with "leukemic form" of disseminated post-transplant lymphoproliferative disorder - Saadiya Haque; Bhaskar Kallakury; Aziza Shad; Kristen Snyder (MDPI AG, 2010)
Post-transplant lymphoproliferative disorder (PTLD) represents an abnormal lymphoid proliferation that occurs in recipients of solid organ or bone marrow allograft. It includes a diverse group of diseases ranging from polymorphic B-cell hyperplasia to frank malignant lymphoma. Clinical presentation is variable, ranging from asymptomatic to generalized lymphadenopathy, mononucleosis-like syndrome, nodal or extranodal tumors (usually gastrointestinal tract), systemic lymphomatous involvement, and rare (less than 1% of cases) fulminant disseminated disease. PTLD is more common in children than in adults. Younger patients usually present with mononucleosis-like symptoms. We present an unusual case of a 5-year old male who developed a widely disseminated leukemic form of PTLD, involving lymph nodes, tonsils, multiple organs, bone marrow, cerebrospinal fluid, and peripheral blood.